The earliest documents in Old Javanese - Griffiths, Arlo; Nastiti, Titi Surti; Sastrawan, Wayan Jarrah (UI Scholars Hub, 2025)
This short contribution presents two recently discovered inscriptions from Central Java that are among the oldest documents in the Old Javanese language, namely a dated stone from Kesongo (685 Śaka/743 CE) and the Disunuh inscription (709 Śaka/787 CE). These two artefacts constitute new evidence that Old Javanese had become a written language in this part of Java already in the eighth century CE. Previously, the period of use of Old Javanese in epigraphy was reckoned to have begun in the ninth century, and in East Java, based on the Harinjing A inscription from Kediri, assumed to date to 726 Śaka/804 CE. The new discoveries require a revision of the chronology of the emergence of vernacular epigraphy on the island of Java.